Students' Perception on the Implementation of Small Group Discussion in English Speaking Activity (A Study at SMP N 1 Palembayan) - Nola Indah Permata Putri; Hamzah Hamzah (Journal of English Language Teaching, 2022)
Small Group Discussion is one of the techniques in the teaching and learning process such as for English speaking class. This study was conducted to find students’ perception on the implementation of small group discussion in English speaking class. This study used descriptive research. The data was collected by using, questionnaire, and interview. The participants of this study were the students of the second grade of SMP N 1 Palembayan. It consisted of three classes that are taught by a teacher. There were 95 students in the academic year 2022/2023. The result of this study showed that students had a positive perception on the implementation of small group discussion in English speaking class with a percentage of 52% in the excellent category and 48% in the good category